A transcriptionally and functionally distinct PD-1+ CD8+ T cell pool with predictive potential in non-small-cell lung cancer treated with PD-1 blockade. (July 2018) - Thommen, Daniela; Koelzer, Viktor; Herzig, Petra; Roller, Andreas; Trefny, Marcel; Dimeloe, Sarah; Kiialainen, Anna; Hanhart, Jonathan; Schill, Catherine; Hess, Christoph; Savic Prince, Spasenija; Wiese, Mark; et al.
Abstract Evidence from mouse chronic viral infection models suggests that CD8+ T cell subsets characterized by distinct expression levels of the receptor PD-1 diverge in their state of exhaustion and potential for reinvigoration by PD-1 blockade. However, it remains unknown whether T cells in human cancer adopt a similar spectrum of exhausted states based on PD-1 expression levels. We compared transcriptional, metabolic and functional signatures of intratumoral CD8+ T lymphocyte populations with high (PD-1T ), intermediate (PD-1N ) and no PD-1 expression (PD-1– ) from non-small-cell lung cancer patients. PD-1T T cells showed a markedly different transcriptional and metabolic profile from PD-1N and PD-1– lymphocytes, as well as an intrinsically high capacity for tumor recognition. Furthermore, while PD-1T lymphocytes were impaired in classical effector cytokine production, they produced CXCL13, which mediates immune cell recruitment to tertiary lymphoid structures. Strikingly, the presence of PD-1T cells was strongly predictive for both response and survival in a small cohort of non-small-cell lung cancer patients treated with PD-1 blockade. The characterization of a distinct state of tumor-reactive, PD-1-bright lymphocytes in human cancer, which only partially resembles that seen in chronic infection, provides potential avenues for therapeutic intervention. Tumor-infiltrating CD8+ T cells with high expression of PD-1 in non-small-cell lung cancer are distinct from exhausted T cells in chronic virus infection, have high tumor reactivity and associate with response to PD-1-targeted immunotherapy.